The Simulation and Analysis on Die Casting Process of Copper Rotors - Dong Liang; Jingyuan Bai; Xujun; Mi; Victor Zhou (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
Squirrel cage induction motors are the mostly used motors at present. Currently, the rotors of the squirrel cage induction motors are produced by aluminum die casting technique with the advantages of low cost of rotors. It is well known that the copper’s electrical conductivity is around 40% higher than that of aluminum. If copper is used to replace the current widely used aluminum in rotors, the total loss of motors will be reduced, hence increasing the overall motor efficiency. Copper rotors can be used to produce high efficiency and even super premium efficiency motors without enlarge the motor frame size. Considering the huge quantity of motors, the die casting process is the best solution to produce copper rotor with economic cost. Because of the characteristics of copper, it is difficult to produce copper rotors by casting similar to that done in aluminum rotors. In order to improve the die casting quality of copper rotor, a new tooling structure was developed and the casting process of copper rotor was simulated and analyzed by Any-casting software. The filling process, solidification process, inner gas distribution and residual melt modulus were analyzed. It was found that the design of symmetrical runner and inner runner on both sides was helpful to reduce the impact of molten copper to the cavity surface during the filling process. The use of Slag traps array can reduce die casting defects inside the end rings. That will be helpful to improve the rotor quality. INTRODUCTION Squirrel-cage AC induction motors are most widely used in the world. In 2017, the total installed capacity of AC motors in China has reached more than 1.2 billion kW, and the annual power consumption accounts for about 60% of the total national electricity consumption. To improve the efficiency of squirrel-cage motor will be helpful to energy conservation and environment protection. There are several ways to improve efficiency of induction motors, using copper rotor is one of the most effective solutions. It is well known that the copper’s electrical conductivity is around 40% higher than that of aluminum. If copper is used to replace the current widely used aluminum in rotors, the total loss of motors will be reduced, hence increasing the overall motor efficiency. Copper rotors can be used to produce high efficiency and even super premium efficiency motors without enlarge the motor frame size.